Multistakeholder Perceptions of Priorities in Primary Care as a Source of Local Innovation: Qualitative Descriptive Study - Gerri Lamb PhD, RN, FAAN; Jane Hook MS, RN; Richard Kratche MD, FAAFP; Kristen K. Will PhD, PA-C; David Coon PhD; Nina Karamehmedovic BA (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The purpose of this qualitative descriptive study was to compare the needs and priorities of multiple stakeholder groups as a source of local innovation to improve primary care. Focus groups were conducted with 44 members of 7 primary care stakeholder groups associated with a large health system and its academic and community networks. Data were analyzed using directed content analysis. Initial categories for the content analysis were drawn from the Clinical Learning Environment Review (CLER 2.0) framework. Three CLER 2.0 concepts, quality health care, teaming, and wellbeing were central to an optimal primary care experience for all groups. Quality health care was the top priority across groups. Shared themes included having meaningful relationships and achieving healthy outcomes. While all groups perceived teaming and wellbeing as important, each stakeholder group had different priorities. Willingness to engage in teaming was conditional on its ability to meet both shared and unique needs. Our findings suggest that shared priorities among primary care stakeholder groups provide a robust foundation for local innovation. Understanding differences in priorities is necessary to identify conditions of engagement across groups. Creative integration of common and unique priorities is key to sustainable local innovation.